Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acsami.3c09114
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrastable Bifunctional Electrocatalyst Derived from a Co2+-Anchored Covalent–Organic Framework for High-Efficiency ORR/OER and Rechargeable Zinc–Air Battery

Abstract: It remains a great challenge to develop alternative electrocatalysts with high stability for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Herein, a bifunctional electrocatalyst composed of hollow CoO x (Co 3 O 4 /CoO) nanoparticles embedded in lamellar carbon nanofibers is derived from a Co 2+ -anchored covalent−organic framework. The asfabricated electrocatalyst (CoO x @NC-800) exhibits a half-wave potential (E 1/2 ) of 0.89 V with ultrahigh long-term stability (100% current retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…For example, Kuang et al reported a bimetallic Co− Cu−Co-decorated carbon nanosheet for the zinc−air battery with an OCV of 1.424 V, a peak power density of 104.3 mW/ cm 2 , and a specific capacity of 771.7 mAh/g Zn with a voltage gap of 0.85 V when cycled at 10 mA/cm 2 . 65 Similarly, Li et al claimed a Co 2+ -anchored covalent−organic framework-based battery with an OCV of 1.46 V and long cycling for a period of 200 h at 10 mA/cm 2 but with a higher voltage gap of 0.87 V. 66 Though Gopalakrishnan et al reported a longer cycling performance of 370 h for CoS/Co−N x /CoNi/NiS catalystbased batteries, their corresponding voltage gap was reported to be higher (0.96 V). 67 Li et al attempted to alloy Co species into ordered and interconnected macroporous carbon polyhedra and utilize them as a cathode for a rechargeable zinc−air battery with a very low potential gap of 0.6 V, but the charge−discharge operation was carried out at a very low current density of 2 mA/cm 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kuang et al reported a bimetallic Co− Cu−Co-decorated carbon nanosheet for the zinc−air battery with an OCV of 1.424 V, a peak power density of 104.3 mW/ cm 2 , and a specific capacity of 771.7 mAh/g Zn with a voltage gap of 0.85 V when cycled at 10 mA/cm 2 . 65 Similarly, Li et al claimed a Co 2+ -anchored covalent−organic framework-based battery with an OCV of 1.46 V and long cycling for a period of 200 h at 10 mA/cm 2 but with a higher voltage gap of 0.87 V. 66 Though Gopalakrishnan et al reported a longer cycling performance of 370 h for CoS/Co−N x /CoNi/NiS catalystbased batteries, their corresponding voltage gap was reported to be higher (0.96 V). 67 Li et al attempted to alloy Co species into ordered and interconnected macroporous carbon polyhedra and utilize them as a cathode for a rechargeable zinc−air battery with a very low potential gap of 0.6 V, but the charge−discharge operation was carried out at a very low current density of 2 mA/cm 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, Kuang et al reported a bimetallic Co–Cu–Co-decorated carbon nanosheet for the zinc–air battery with an OCV of 1.424 V, a peak power density of 104.3 mW/cm 2 , and a specific capacity of 771.7 mAh/g Zn with a voltage gap of 0.85 V when cycled at 10 mA/cm 2 . Similarly, Li et al claimed a Co 2+ -anchored covalent–organic framework-based battery with an OCV of 1.46 V and long cycling for a period of 200 h at 10 mA/cm 2 but with a higher voltage gap of 0.87 V . Though Gopalakrishnan et al reported a longer cycling performance of 370 h for CoS/Co–N x /CoNi/NiS catalyst-based batteries, their corresponding voltage gap was reported to be higher (0.96 V) .…”
Section: Resultsmentioning
confidence: 99%